MANUSIA BALI DALAM NOVEL TARIAN BUMI KARYA OKA RUSMINI: TINJAUAN ANTROPOLOGI SASTRA - Tukur Novitasari; Rusdian Noor Dermawan (Universitas Sarjanawiyata Tamansiswa, 2014)
This study aimed to describe (1) plots, characters and characterizations, and background (2) in a novel human Bali Tarian Bumi works by using the approach of Oka Rusmini Literary Anthropology. This type of research is descriptive qualitative.The research data in the form of units of events that contains information about plots, characters and characterizations, and background as well as human Bali with all the attitude and behavior. Sources of data in this study are novel Tarian Bumi. The data collection was done by observing the novel Tarian Bumi. The research instrument is the researcher himself. The technique of data analysis is descriptive qualitative techniques. The technique used for the data in this study is a unit which is a novel event in the qualitative data. The explanation in this study conducted descriptive trying to show a description of the things that show plots, characters and characterizations, and background, as well as in the novel human Bali Tarian Bumi. The research results are as follows. (1) The flow of the mixture, the beginning of the story opens with the story of the lake becomes a Sudra woman, then Ponds uncover the veil of the past, and the story ends with the story of Ponds became Sudra woman. The main character Ida Ayu Telaga Pidada qualified as the main character because it most closely linked to the theme, a lot of interaction with other characters, and the frequency of occurrence of most. Faithful characterizations. Background on the island of Bali. (2) Human Bali with all the wealth of culture that is reflected in the form of (a) the system of language in the novel Dance of the Earth may indicate differences in social class, (b) knowledge of the system can be understood from the traditional way of thinking and modern ways of thinking, (c) the social system or social organization indicated by the customary rules that must be obeyed, (d) living equipment systems and technology in the novel dances Earth demonstrate differences in social class, (e) livelihood systems can also indicate differences in social class, (f) religious belief system or not regardless of religious ceremonies, (g) art systems include Balinese dance and painting.